The Danish opt-out: Doctrinal issues, future challenges and Nordic implications - Arvig Verdoner, Søren (Nordisk Tidsskrift for Kriminalvidenskab, 2025)
Abstract: This article examines the scope of the Danish opt-out within the field of EU criminal law. It analyzes the historical and legal origins of the opt-out and provides a doctrinal assessment of key issues concerning its scope, including the significance of judgments from the Court of Justice of the European Union rendered within the framework of the opt-out. Subsequently, Denmark’s position is compared with that of the other Nordic countries, concluding that Denmark’s relationship to EU criminal law is closely comparable to Norway’s. Finally, the article identifies key future challenges that Denmark may face due to its position outside the EU criminal law cooperation. It argues that Denmark’s non-participation in the development of a common EU standard for criminal procedural rights may affect its ability to participate in EU instruments founded on the principle of mutual trust. I denne artikel undersøges rækkevidden af det danske retsforbehold på det strafferetlige område. Artiklen analyserer rets forbeholdets historiske- og juridiske oprindelse, og leverer en retsdogmatisk gennemgang af centrale problemstillinger vedrørende dets anvendelsesområde, herunder betydningen af domme fra EU-Domstolen, der afsiges indenfor for rammerne af retsforbeholdet. Herefter sammen holdes Danmarks position med de øvrige nordiske landes. Det konstateres, at Danmarks status i forhold til EU-straffe retten i vidt omfang kan sammenlignes med Norges. Afslutningsvist udpeges en række fremtidige udfordringer, som Danmarks position uden for EU-strafferetssamarbejdet kan medføre. Det konkluderes, at Danmarks manglende deltagelse i opbygningen af en fælles EU-standard for strafprocessuelle rettigheder potentielt kan få konsekvenser for Danmarks mulighed for at deltage i EU-instrumenter, der bygger på princippet om gensidig tillid (mutual trust).